THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION ON READINESS TO CHANGE WITH LEARNING ORGANIZATIONS AS INTERVENING VARIABLES (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
Readiness to change is an important part that every organization must have in facing the era of industry 4.0. This study aims to analyze the mediating impact of organizational learning in strengthening the influence of transformational leadership and job satisfaction on readiness to change. The population and sample of the research are employees of the Department of Transportation and the Department of Communication and Information in the city of Padang, totaling 107 employees. This study uses structural equation model models (SEM) with SmartPLS 3 analysis tools. The results of the study concluded that transformational leadership, job satisfaction and learning organization have a positive and significant influence on readiness to change. Furthermore it was also found that transformational leadership and job satisfaction also had a significant effect on learning organizations. The mediating effect in the study found that the learning organization variable was able to provide an additional influence on transformational leadership and job satisfaction in strengthening its influence on readiness to change.